Familial Aggregation of High Tumor Necrosis Factor Alpha Levels in Systemic Lupus Erythematosus. (25th September 2013) - Mangale, Dorothy; Kariuki, Silvia N.; Chrabot, Beverly S.; Kumabe, Marissa; Kelly, Jennifer A.; Harley, John B.; James, Judith A.; Sivils, Kathy L.; Niewold, Timothy B.
Abstract : Systemic lupus erythematosus (SLE) patients frequently have high circulating tumor necrosis factor alpha (TNF- α ) levels. We explored circulating TNF- α levels in SLE families to determine whether high levels of TNF- α were clustered in a heritable pattern. We measured TNF- α in 242 SLE patients, 361 unaffected family members, 23 unaffected spouses of SLE patients, and 62 unrelated healthy controls. Familial correlations and relative recurrence risk rates for the high TNF- α trait were assessed. SLE-affected individuals had the highest TNF- α levels, and TNF- α was significantly higher in unaffected first degree relatives than healthy unrelated subjects ( P = 0.0025 ) . No Mendelian patterns were observed, but 28.4% of unaffected first degree relatives of SLE patients had high TNF- α levels, resulting in a first degree relative recurrence risk of 4.48 ( P = 2.9 × 10 - 5 ) . Interestingly, the median TNF- α value in spouses was similar to that of the first degree relatives. Concordance of the TNF- α trait (high versus low) in SLE patients and their spouses was strikingly high at 78.2%. These data support a role for TNF- α in SLE pathogenesis, and TNF- α levels may relate with heritable factors. The high degree of concordance in SLE patients and their spouses suggests that environmental factors may also play a role in the observed familial aggregation.